Gamification for Business Process Modeling - Pflanzl, Nicolas (2018)
Gamification is a novel, industry-driven trend that is concerned with the application of game design elements to non-game contexts. The main goal of this work is to examine how gamification can be used to support business process modeling. To that extent, design science research was conducted to determine current challenges and problems in business process management that may be solved through gamification. To address these issues, a “gamified” version of the Horus Business Modeler – a software for process modeling – was designed, implemented, and evaluated. The results of the evaluation are mixed and show increases in model quality and tool assessment, but no impact on motivation. Overall, this work contributes to research by providing insights into the impacts of gamification in a domain not previously discussed, and by showing how certain issues of business process management can be addressed by means of an IT artifact with particular characteristics.Permalinkhttps://nbn-resolving.de/urn:nbn:de:hbz:6-29169441136ISBN978-3-8405-0176-0Paperback, XIX, 514 Seiten